Wanted Dead or Alive - Sanders, Cheryl (Pneuma, 2014)
This essay explores the relationship between black theology and renewal theology and assesses the ongoing relevance of black theology to the mission and future of the black churches. Recent writings by Eddie Glaude, Raphael Warnock, James Cone, and Peter Paris are considered in conversation with the works of Brian Bantam, J. Kameron Carter, and Willie Jennings, whose imaginative attention to Christology, pneumatology, and ecclesiology provokes thoughtful engagement of issues of race, gender, power, and privilege in the context of renewal and the global impact of Pentecostalism more than a century after the Azusa Street Revival led by William J. Seymour.